Perlindungan Hukum Pekerja di Indonesia melalui Pemenuhan Jaminan Sosial - Mustafa, Afi Luthfi; Kusmiran, Adhe Clara; Fajrin, Fauziah; Manalu, Ezrayanti (DPPM Universitas Pelita Bangsa, 2025)
This study examines legal protection for workers in cases of BPJS Ketenagakerjaan contribution arrears by companies and its implications for workers' rights. Corporate non-compliance not only harms workers but also threatens the stability of national social security. The study uses a normative juridical method with a statutory regulatory approach, primary data sources from related laws and regulations, and secondary data from books, journals, and articles. The results show that companies that are in arrears in contributions can be subject to administrative, criminal, and civil sanctions, including fines, restrictions on public services, imprisonment, or compensation. The study emphasizes the role of BPJS Ketenagakerjaan, labor inspectors, and the Attorney General's Office in ensuring company compliance and the need for good faith in resolving arrears. The findings emphasize the need for strict law enforcement for the welfare of workers